The effectiveness of fintech in non-cash transaction in banking services - Cindy, Cindy; Arifin, Agus Zainul; Simanjuntak, Sri Ida Royani (Journal of Commerce, Management, and Tourism Studies, 2024)
The purpose of this study is to verify the relationship between the effects of transaction processes and seamless transactions on perceived benefits. The problem approach uses Theory Acceptance Model (TAM). The research uses primary data obtained by distributing questionnaires online. Data collection method with purposive sampling of data collected 545 respondents. Data were analyzed by SEM-PLS. The results of the study prove that transaction processes and seamless transactions have a positive effect on perceived benefits. The original value of this study proves that the TAM theory is able to explain the relationship between variables from the research model that was built.